Comparison between estimated and measured myopia progression in Hong Kong children without myopia control intervention. (1st October 2021) - Yang, Yajing; Cheung, Sin Wan; Cho, Pauline; Vincent, Stephen J
Abstract: Purpose: To compare myopia progression estimated by the Brien Holden Vision Institute (BHVI) Myopia Calculator with cycloplegic measures in Hong Kong children wearing single‐vision distance spectacles over a 1‐ and 2‐year period. Methods: Baseline age, spherical equivalent refraction (SER) and ethnicity of control participants from previous longitudinal myopia studies were input into the BHVI Myopia Calculator to generate an estimate of the SER at 1 and 2 years. Differences between the measured and estimated SER (116 and 100 participants with 1‐ and 2‐year subjective refraction data, respectively, and 111 and 95 participants with 1‐ and 2‐year objective refraction, respectively) were analysed, and the measured SER compared with the 95% confidence interval (CI) of the estimated SER. Results: In children aged 7–13 years, 36% progressed within the 95% CI of the Myopia Calculator's estimate, whereas 33% became less myopic than predicted (range 0.31 to 1.92 D less at 2 years) and 31% became more myopic than predicted (range 0.25 to 2.33 D more myopic at 2 years). The average difference between the estimated and measured subjective or objective SER at 1 and 2 years of follow‐up was not clinically significant (<0.25 D). Conclusions: On average, the BHVI Myopia Calculator estimated SER was in close agreement with measured cycloplegic SER after 1 and 2 years of follow‐up (mean differences < 0.25 D). However, the measured myopia progression only fell within the 95% CI of the estimated SER for 32%–38% of children, suggesting that the BHVI 'without management' progression data should be interpreted with caution. The inclusion of additional data, modified to include axial elongation, from longitudinal studies of longer duration with larger sample sizes and a range of racial backgrounds may improve the Calculator's ability to predict future myopia progression for individual children.